Respostas
respondido por:
1
vamos lá!
(2x-6).(x-5)>0
2x^2-10x-6x+30>0
2x^2-16x+30>0
a=2
b=-16
c=30
∆=b^2-4.a.c
∆=(-16)^2-4.(2).(30)
∆=256-240
∆=16
x'=16+4/2.(2)
x'=20/4
x'=5
x"=16-4/4
x"=12/4
x"=3
x'=5 e x"=3
S={x e |R/x<3 ou x>5}
Espero ter ajudado!
boa noite!
(2x-6).(x-5)>0
2x^2-10x-6x+30>0
2x^2-16x+30>0
a=2
b=-16
c=30
∆=b^2-4.a.c
∆=(-16)^2-4.(2).(30)
∆=256-240
∆=16
x'=16+4/2.(2)
x'=20/4
x'=5
x"=16-4/4
x"=12/4
x"=3
x'=5 e x"=3
S={x e |R/x<3 ou x>5}
Espero ter ajudado!
boa noite!
Anexos:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás